HDR Syndrome Accompanying Type 1 Diabetes Mellitus and Hypopituitarism - Mustafa Can; Feridun Karakurt; Muhammed Kocabas; İlker Cordan; Melia Karakose; Mustafa Kulaksızoglu (Case Reports in Endocrinology)
HDR (Hypoparathyroidism, Deafness, and Renal Dysplasia) syndrome is an autosomal dominant disorder characterized by the triad of hypoparathyroidism, sensorineural deafness, and renal disease. Approximately 65% of patients with HDR syndrome have all three of these features, while others have different combinations of these features. We aimed to present a case with primary hypoparathyroidism, hearing loss, and nondiabetic chronic kidney disease and diagnosed as HDR syndrome while being followed up for type 1 diabetes mellitus and hypopituitarism.